Perubahan Nilai Kekerasan Pelat Baja Kapal Dengan Perlakuan Bending Line Heating - Fakultas Teknik Universitas Diponegoro Semarang), Sulaiman, Eko Julianto S. (Program Diploma III Tek (Teknis, 2015)
The process of bending steel hull plate was needed to form a body vessel in accordance with the outline plan drawings (body plan) in order to obtain the form that streamlines the hull. This bending process can be done with the cold and the heating method of lines (line heating). Bending line heating method is very beneficial economically, but have several problems, especially in setting the proper heating temperature in the heating process of his line. Heating is provided when line heating the plate hardness value can be changed. This study aims to analyze the influence of cold bending and line heating to changes : hardness value of material. The research method is a laboratory experiment is conducted using the test object (specimen) plate steel AISI-E2512, which treated the cold bending and bending line heating using three kinds of bending radius ofÂ  R.67, R.100, R.133 and hardness testing method Rockwell. The result showed that the treatment process of line heating causes an increase in hardness values of specimens are on average 14.31% and specimens only in cold bending hardness value increased by an average 9.04% of the normal plate hardness conditions.Keywords: Bending line heating, Hardness value